St. Thomas Aquinas’s Teaching on Love as a Component of Karol Wojtyła’s Project of Finding an Adequate Interpretation of the Love Between a Man and a Woman - Karol Petryszak (Studia Gilsoniana)
The article presents a hitherto unknown lecture by Karol Wojtyła in 1954, discussing St. Thomas Aquinas’ teaching on love. Wojtyła juxtaposes this teaching with the philosophy of Max Scheler and unequivocally argues for a Thomistic understanding of love. In the article, I discuss how Wojtyła understood love in general after St. Thomas and then situate love between a man and a woman within its framework. The conclusion of this juxtaposition and the argumentation is that only multidimensional love between a man and a woman can adequately perfect their natures. Other relationships that mimic the complete love of a man and a woman cannot adequately perfect either side of the relationship. In addition, due to the nature of the material on which the article’s argumentation is based, historical and philosophical issues that shed significant light on the development of Wojtyla’s teaching on love – especially in the 1950s – are also presented.